ANALISIS KARAKTERISTIK, PENGETAHUAN, DAN SIKAP PERAWAT TERHADAP PERAWATAN PALIATIF DI RUMAH SAKIT DAERAH KABUPATEN SUBANG - Fitri Handayani; Iis Neneng Rosita (Journal Keperawatan, 2022)
Palliative care cannot be done by just anyone, because it must involve a special team such as doctors, nurses, and other medical experts who are professionals in the field of palliative specialization. The purpose of this study is to be able to analyze the relationship between the level of knowledge and the attitude of nurses about palliative care to the characteristics in the Subang Regency Regional Hospital. The research design used is Cross Sectional. The sample in this study was 76 respondents. Univariate, bivariate data analysis using chi square and multiple logistic regression multivariates. The results showed that the variables that had a meaningful relationship with nurse actions in valiative care were variables of age, education, knowledge, and attitudes with a p value of < 0.05. Of the four variables, there is a chance of palliative care implementation of 67.5%. It is necessary to improve knowledge and attitudes in the field of palliative care for nurses who provide palliative care through special education.